FLOWERING AND FRUIT YIELD OF THE ITALIAN ABOBRINA 'DAIANE' UNDER APPLICATION OF VEGETABLE REGULATOR AND FOLIAR FERTILIZER - de Matos, J. P.; Correia, E. C. S. S.; Monteiro, R. N. F.; Domingues Neto, F. J.; da Silva, D. P. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Italian zucchini, plant of the cucurbit family, is among the ten vegetables of greatest economic value and of greater production in Brazil. The growing demand in recent years for high food quality has encouraged the use of new production technologies, such as the use of plant regulators and foliar fertilizers. Thus, the objective of this work was to evaluate the effect of foliar application of the plant regulator Biozyme® TF and K-fol® foliar fertilizer, associated or not, on the flowering and fruit yield of zucchini 'Daiane'. The experimental design was in randomized blocks, with six treatments: Control (0 mL L-1); Biozyme® TF (1.0 ml L-1); Biozyme® TF (2.0 ml L-1); Biozyme® TF + K-fol® (1.0 ml L-1 + 1.0 g L-1); Biozyme® TF + K-fol® (2 ml L-1 + 2.0 g L-1) and K-fol® (2.0 g L-1) and four blocks, totaling 24 experimental plots with ten plants each. The variables of zucchini analyzed were: number of male and female flowers and average fruit weight. The evaluations concerning the quantification of flowering and the yield were conducted every four days, beginning 30 days after transplantation and extending for 40 days, totalizing 10 evaluations. There was a significant increase in the number of flowers and the average weight of zucchini fruits by the isolated or associated application of the plant regulator Biozyme® TF and K-fol® foliar fertilizer.